The nature and role of morality in situational action theory. (November 2022) - Barton-Crosby, Jennifer
For situational action theory (SAT), morality is key to the definition of crime and the explanation for why and how acts of crime happen: acts of crime are acts of moral rule-breaking and personal morality guides individuals' perception of moral rule-breaking as an option before controls become relevant. However, the nature and role of morality in SAT can be misread. Within this article I respond to misinterpretations of the theory by elaborating and adding further context to the concept of morality in SAT. I contend that the root of misunderstanding is grounded in alternative assumptions regarding human nature: SAT assumes a fundamentally rule-guided human nature, whereas the prevailing view within criminology is that people are primarily self-interested. In this article I delineate SAT's assumption of a rule-guided human nature and set out how this assumption informs the definition of crime and personal morality in the theory. I further specify the nature and role of morality in the perception of action alternatives, and in so doing distinguish SAT from theories that view constraint as the measure of morality. Finally, I develop and clarify SAT's position on the relationship between morality and the law.